Pengaruh Kepemimpinan, Keadilan Distributif Kompensasi, Kebutuhan Berprestasi, Kebutuhan Berafiliasi, Dan Kebutuhan Kekuasaan Terhadap Kinerja Karyawan Di Rumah Sakit Umum Daerah Kalianda - Ghozan Pitra Wisashina (Universitas Muhammadiyah Yogyakarta, 2013)
The author examines the influence of leadership, distributive judgement of compensation, need for achievement, need for affiliation, and need for power, on the performance of employees of RSUD Kalianda. The performance of employee will affect the performance of companies that also affect the company achieve its goals, vision and mission. Leves of employee performance is inseparable from the role of employee in managing employees associated factors of leadership, namely how the level of influence and effectiveness of leadership undertaken, the distributive judgement of compensation factor, namely the extent to which the role and influence of the distributive judgement of compensation system applied in improving the performance of its employees, and motivate reflection of need for achievement, need for affiliation, and power needs that exist within themselves and therefore contributes to the achievement of its performance. Population in this study around 291 peoples, with 63 peoples as sample. Independent variables: leadership, distributive judgement of compensation, need for achievement, need for affiliation, need for power. Dependent variables: the performance of employee who judged from employee appraisal. This study uses questionnaire instruments data that have proven validity and reliability, and interview. The statistical techniques using multiple linear regression analysis with the partial test and coefficient of determination (R2). The results that the variables of need for affiliation has a positive significant impact on the performance of employee. While the variables of leadership, distributive judgement of compensation, need for achievement, and need for power are not having a significant effect on the performance of employee. Independent variables in this study are efficient enough to explain its influence on the dependent variable, is attested by the value of the coefficient of determination (R2) from the second regression analysis is 0.272 had the significant level 0.000.